A novel laser powder bed fusion Al-Fe-Zr alloy for superior strength-conductivity trade-off. (October 2022) - Pauzon, Camille; Buttard, Maxence; Després, Arthur; Chehab, Béchir; Blandin, Jean-Jacques; Martin, Guilhem
Abstract: New aluminium alloy design strategies for laser powder bed fusion (LPBF) are needed to target high strength and conductivity applications and substitute the traditional 6xxx series which suffers from hot cracking during LPBF processing. This study presents the route followed to design a novel Al-Fe-Zr alloy offering good processability, superior yield strength (310 MPa) and thermal conductivity (180 W/m·K) after direct ageing (400°C/4h). The multi-scale characterization, combining scanning and transmission electron microscopy with automated crystallographic orientation mapping and energy dispersive spectroscopy, reveals the precipitation of plate-like Al13 Fe4 and coherent Al3 Zr-L12 nanoprecipitates upon ageing, enhancing the material's strength. In turn, the associated solid solution depletion results in a significant conductivity increase. The strategy to select low vapour pressure elements and slow diffusers in Al, as well as the low solubility of Fe in Al demonstrates the ability through alloy design for additive manufacturing to fill gaps in the material property space. Graphical abstract: Image, graphical abstract